THE ART OF HAILING BLACK EMANCIPATION BY CAPSIZING THE REPERCUSSIONS OF WHITE DETERMINISM IN RICHARD WRIGHT’S NATIVE SON AND RALPH ELLISON’S INVISIBLE MAN - Agneshia, A. Rosy; Albert, Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The determining laws of external force and the concept of free will are perceived to be intricate while striving to exhibit a simple and confined elucidation for they comprise every single thing that goes by their appellation when examined with the aid of naturalism and existentialism. These philosophies take involuted peregrinations leading to the vivid comprehension of the relationship between man and his environment. The naturalists navigate far beyond realism intending to get in line with determinism and also claim that a person is organically an animal devoid of free will. Conversely, the existentialists revere ‘man’ as their protagonist, thereby reputing him with freedom of choice, self-creation, responsibility, consciousness and individuality. The works of African American writers that flaunt the spirit of existentialism can be witnessed as a result of their protagonists’ unadaptable restraints whose lives are usually a mare’s nest. This research article culls out Wright’s Native Son and Ellison’s Invisible Man to cram it up with the unadulterated existential value over the harsh realities of naturalism which is an attempt to make the blacks indomitable and thereupon leading one to contemplate over the universal query; does an individual exhibit his individuality or is forcefully made to establish the chores assigned by the natural determinants?